Pengaruh Strategi Promosi yang diterapkan pada Restoran Casa Luna terhadap penjualan makanan dan minuman - Agung Permana Budi; I Nengah Laba (Institut Pariwisata dan Bisnis Internasional, 2010)
Competition among restorans to provide the best and deserve to be his guest with a variety of business and strategy, especially regarding the promotion strategies that have been set by management in accordance with a characteristic that is owned and objectives to be achieved.The Casa Luna Restoran is located in the tourist area of Bali Ubud is the object of research, on the basis of initial observations that have been done already obtained data on the number of visits of guests from January to December 2009 decreased the number of arrivals is very significant that there was a problem inside the restoran.The factors that lead to not achieving the sales targets, quality staff, quality food, quality service, facilities and promotion by the restoran. From the above explanation can be concluded that the decline in guest visits to eat and drink at the Casa Luna Restoran is predicted because of the promotion.The test results Coeficien of regression in Table 4.3, shows that, variables self promotion (X1) and personal selling (X2) shown significant influence with number X1 of 0045 against the dependent variable is Y and X 2 = 0.000, above shows the differences are not significant (the value significantly above the cut- off value 0.05), while the variables X3 and X4 variable no effect on sales at the show with with a number above 0005, which states there is the influence of Ho campaign strategy against the arrival of guests and sale of food and beverages can be accepted is indicated by each variable X1 (self promotion) and X2 (personal selling).